"MODERN PEDAGOGICAL-PSYCHOLOGICAL APPROACHES TO DEVELOPING ATTENTION STABILITY AND MENTAL HEALTH IN EARLY SCHOOL STUDENTS IN THE ERA OF GLOBALIZATION." (Universal International Scientific Journal, 2026)
: This article studies the role of the attention process in the cognitive sphere of primary school students (7-11 years old) and its specific psychological characteristics. During the study, the mechanisms of transition from involuntary to voluntary attention, the stability, mobility and distribution of attention, the influence of such features on the effectiveness of educational activities were analyzed. Also, the problems of attention deficit in children during the period of adaptation to the school environment and psychological correction methods for their elimination are highlighted. The article provides scientific and methodological recommendations for primary school teachers and school psychologists.
Keywords: : Attention, voluntary attention, primary school age, cognitive development, sensory processes, attention stability, learning motivation, psychological correction.